2013
DOI: 10.1002/mc.22093
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin influences vascular permeability via Wnt/β-catenin pathway

Abstract: Wogonin, a flavone from the root of Scutellaria baicalensis Georgi, has shown various biological activities. In our previous study, it was confirmed that wogonin could decrease the expression of hypoxia-inducible factor-1α (HIF-1α) by affecting its stability under hypoxia. However, it is still unknown whether wogonin could influence Wnt/β-catenin pathway under hypoxia. In this study, we found that wogonin disrupted Wnt/β-catenin signaling and reduced the secretion of vascular endothelial growth factor (VEGF, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Indeed, previous studies have shown an activation of Wnt/β-catenin pathway under hypoxic conditions and an increase in vascular permeability in response to an hypoxic insult. 31 , 32 Furthermore, a recent study by Lim et al. 33 has underlined the role of endoneurial hypoxia resulting from peripheral nerve injury in the genesis of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown an activation of Wnt/β-catenin pathway under hypoxic conditions and an increase in vascular permeability in response to an hypoxic insult. 31 , 32 Furthermore, a recent study by Lim et al. 33 has underlined the role of endoneurial hypoxia resulting from peripheral nerve injury in the genesis of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…We found OA could down‐regulate LiCl‐indcued p‐GSK‐3β as well, which indicated OA could promote the activation of GSK‐3β. Interestingly, wogonin could also inhibit Wnt/β‐catenin in our previous research, which suggests that this type of flavonoids promises to be an inhibitor in Wnt/β‐catenin .…”
Section: Discussionmentioning
confidence: 62%
“…Owing to this data, we believe that the diminished NF-κB activity demonstrated in this and separate (Xu et al, 2017) instances caused by wogonin comes through a modulatory effect on ciliary signaling. In addition to this data, it is known that wogonin has been demonstrated in separate instances to have inhibitory activity on SHH (Owen et al, 2017) and WNT signaling (Song et al, 2015), processes which are upregulated in osteoarthritis (Luyten et al, 2009;Chang et al, 2012) and mediated by the primary cilium. The fact that wogonin directly counters these pathways with strong connections to the primary cilia and possesses antiosteoarthritic activity strongly suggests that wogonin exerts some sort of corrective action on the primary cilia, and future research should focus on interactions between wogonin and ciliary homeostasis.…”
Section: Wogonin On the Primary Ciliummentioning
confidence: 76%